A comparative therapeutic evaluation of topical Ivermectin Vs topical Permethrin for the management of scabies - Ankit Srivastava; Sunil kumar Gupta; Mohd Faisal; Farrukh Kidwai; Deepak Kumar; Dibya deb Ghosh; Niaz Ahmed Ansari (International Journal of Medical Research and Review, 2017)
Objective: To compare the therapeutic efficacy of topical ivermectin 0.5% vs. topical permethrin 5% cream in the treatment of scabies.Methods: This was open labelled, parallel group, prospective and comparative clinical study. Depending on the treatment to be received, there were two study groups comprising 50 patients each. Group 1 patients received topical 5 % Permethrin cream on day 1 and repeat application on 1st week follow up and if required then on second week; Group 2 patients received topical 0.5% Ivermectin cream on day 1 and repeat application on 1st week follow up and if required then on second week. The patient were also given antipruritic drug Tablet levocetirizine in a dose of 5 mg once daily given for 2 to 3 weeks. A total of 50 patients in each group were included in the study.Results: More than half of the patients in both Group 1 (56%) and Group 2 (54%) were below 30 years. More than half of the patients in both Group 1 (54%) and Group 2 (52%) were males. Majority of site of lesions were absent at 2 weeks in both the groups. Moderate and severe itching of lesion became nil at 2 weeks in both the groups. Grade 2 of itching of lesion was in 2% at 2 weeks in both the groups. KOH was positive in 94% patients in Group 1 and in 96% in Group 2 at baseline which decreased to 14% in Group 1 and 18% in Group 2 at 1 week. KOH positivity became nil at 2 weeks in both the groups.Conclusion: Topical Permethrin 5 % and Ivermectin 0.5 % were equally effective in the treatment of scabies up to 2 weeks.